Investigating functions of human group 2 innate lymphoid cells in health and disease - Nahler, J (2021)
Group 2 innate lymphoid cells (ILC2) have emerged as important effectors of type 2 immune responses that contribute to protection against extracellular parasites and tissue repair. Dysregulated ILC2 responses have been implicated in allergic inflammatory disorders such as atopic dermatitis (AD), a chronic inflammatory skin disease associated with epidermal barrier defects and dysregulated type 2 inflammation. However, much remains to be understood regarding ILC2 effector functions, especially in the context of cutaneous inflammation.